LOCAL LOGISTICS AND SPECIFICS OF THE LINGUISTIC COMPLEX IN THE PRACTICE OF FOREIGN LANGUAGE TEACHING IN A NON-PHILOLOGICAL HIGHER EDUCATION INSTITUTION - Письменна, О. О. (Proceedings of National Aviation University (archive), 2021)
The problem of enrollment of linguistic materials in the educational and methodical method is consideredcomplex and clarity in the process of teaching a foreign language in higher technical institutions.